A multicenter retrospective study of clinical features, laboratory characteristics, and outcomes of 166 hospitalized children with coronavirus disease 2019 (COVID‐19): A preliminary report from Iranian Network for Research in Viral Diseases (INRVD). Issue 2 (30th November 2021) - Sedighi, Iraj; Fahimzad, Alireza; Pak, Neda; Khalili, Mitra; Shokrollahi, Mohammad R.; Heydari, Hosein; Movahedi, Zahra; Dashti, Anahita S.; Cheraghali, Fatemeh; Shamsizadeh, Ahmad; Mirkarimi, Mohammadreza; Alisamir, Mohsen; et al.
Abstract: Background: The objectives of this study were to analyze the clinical features and laboratory profiles and risk factors associated with critical illness of children with severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2). Methods: One hundred and sixty‐six coronavirus disease 2019 (COVID‐19) Iranian pediatric patients were recruited through a collaborative research network between March and May 2020. Demographics, clinical, laboratory, and radiological results were obtained from patient files. Results: Of 166 patients, 102 (61%) and 64 (39%) were males and females, respectively. Ninety‐six (57.8%) and 70 (42.2%), had moderate and severe conditions, respectively. Thirty (18%) of patients died. The common symptoms were fever (73%), cough (54%), and shortness of breath, headache decrease in neutrophil and platelet counts; increase values in lactate dehydrogenase, decrease in the blood pH and HCO3 were significantly associated with the disease severity. 54% and 56% of patients showed abnormal radiographic appearance in Chest X‐ray and in chest computed tomography scan, respectively. Sixty‐one (36.7%) of patients were referred to intensive care unit (ICU). The coexistence of comorbidity was the main factor associated with ICU admission, shock, arrhythmia, acute kidney injury, acute respiratory distress syndrome, acute cardiac injury, and death. Conclusions: We describe a higher than previously recognized rate of COVID‐19 mortality in Iranian pediatric patients. Epidemiological factors, such as the relatively high case fatality rate in the country and the presence of underlying diseases were the main factors for the high death rate.